Strategi Manajemen Konflik dalam Interaksi antar Saudara Kandung Ditinjau dari Keyakinan Orangtua, Jenis Kelamin Orangtua, dan Status Sosial Ekonomi Orangtua - Irwan Nuryana Kurniawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
The purpose of this research was to examine whether parental beliefs about managing sibling conflict correlate with the use of parent’s conflict management strategies in sibling interaction and the differences in the use of conflict management strategies in sibling interaction between mother and father. Further, this study examine the contribution of social economic status (SES), which SES is defined in terms of parents’ years of education and monthly family income, on parental conflict management strategies in sibling interaction. Study participants were 160 couples, who have younger children with mean age 7.2 years and older children with mean age 11.5 years. This research used questionnaire methods which contain parents’self informations and psychological scale  to reveal parents’social economic status, parental beliefs about managing sibling conflict, and the use of conflict management strategies in sibling interaction.The result of this research suggests that 1) there is significant relationship between parental beliefs about managing sibling conflict and the use of parent’s conflict management strategies in sibling interaction.; 2) there is no significant difference between mother and father regarding the use of conflict management strategies in sibling interaction; 3) parent’s social economic status influence the difference use of mother’s child-centered conflict management strategies. Parents who received montly family income above Rp 2.000.000,00 and had completed their university education show higher frequency in the use child-centered conflict management strategies than parents who had lower income and lower education. Parent’s social economic status didn’t influence parents’ use of parental control conflict management strategies. Key Word: parental beliefs about managing sibling conflict, parents’sex, parents’social economic status, parents’conflict management strategies in sibling interaction